Evaluation of anti-diphtheria toxoid antibody persistence in school-age children in Jakarta, Indonesia - Santi, Theresia; Prayitno, Ari; Munasir, Zakiudin; Hadinegoro, Sri Rezeki S.; Harahap, Alida Roswita; Werdhani, Retno Asti; Sah Bandar, Ivo Novita; Jo, Juandy; Hegar, Badriul (Indonesian Pediatric Society, 2024)
Background Diphtheria can be effectively prevented by adequate immunization. A combined vaccine against diphtheria toxoid, pertussis, and tetanus toxoid (DPT) is currently used in routine pediatric immunizations. Outbreaks of diphtheria could emerge in Indonesia as a consequence of declining routine vaccination during the COVID-19 pandemic. Objective To analyze the impact of the first (administered at 18-24 months of age ) and second diphtheria boosters (administered at 5-7 years of age ) in retaining protective levels of anti-diphtheria toxoid antibodies. We also investigated for relevant factors associated with anti-diphtheria toxoid antibody titers. Methods This cross-sectional study was conducted in the Senen District of Jakarta, Indonesia. The inclusion criteria were healthy children aged 6 to 7 years with documented history of DPT vaccination. Primary vaccination defined as 3 doses of DPT at age less than 1 year , first booster was DPT vaccination at 18-24 years of age, and second booster was diphtheria-tetanus (DT) vaccination received at 5 to 7 years of age. Peripheral blood specimens were obtained from participating children, after informed consent was provided by their parents. Antibodies against diphtheria in sera specimens were assessed by commercial anti-diphtheria toxoid immunoglobulin G (IgG) enzyme-linked immunosorbent assay. Results There were 154 children included in the study, with a female majority (61%). Overall, specific humoral immunity against diphtheria was observed in 113 children (73.4%). There was no statistical difference in immunity level between genders. Importantly, children who received the first and second diphtheria booster had significantly higher anti-diphtheria antibody level than those who did not receive both diphtheria booster (P<0.001). Conclusion Booster vaccinations are crucial among school-age children in Indonesia to improve their anti-diphtheria immunity and to minimize a risk of diphtheria outbreaks.